Antibiofilm activity of glycolic plant extracts on Klebsiella pneumoniae clinical isolates (Research, Society and Development, 2021)
Objective: Evaluate the anti-biofilm activity of Gymnema sylvestre, Hamamelis virginiana, Juglans regia, Persea americana, Pfaffia paniculata, Rosmarinus officinalis, Stryphnodendron barbatiman and Thymus vulgaris extracts in 3 MDR strains and 1 ATCC (4352) of Klebsiella pneumoniae. Methods: First were made a screening with broth microdilution test, protocol M7-A9, according to CLSI. Extracts that presented values for Minimal Microbicidal Concentration (MMC) were selected for biofilms tests on 96 wells plates. Treatments used concentrations of 25 and 50 mg/mL, after biofilms were measured by biomass and MTT tests and statistically analyzed by ANOVA and Tukey test (p